144 Granulomatous lymphocytic interstitial lung disease (GLILD) in children. (December 2018) - Nademi, Z; Davies, G; Devlin, L; Chavasse, R; Maimaris, J; Gilmour, K; Wallis, C; Pavasovic, V; Worth, A
Abstract : Background: GLILD is defined as lymphatic infiltrates and granulomata in the lung and is mostly described as a complication of Common Variable Immunodeficiency (CVID). About 58% of patients with CVID develop GLILD and it is associated with early mortality in adults. Method: We describe the clinical, pathological and radiological features of patients using our electronic database in Great Ormond Street Hospital. Results: Six patients were identified: Males and females were equally affected. The age ranged between 4–9 years when the first biopsy confirmed granulomata. They presented with cough (4/6), lymphadenopathy (4/6), hepatosplenomegaly (3/6), Idiopathic Thrombocytopenic Purpura (ITP) (2/6) and recurrent fever (1/6). They all had ground glass reticular appearance with widespread nodules on chest CT scan. The biopsy confirmed non-caseating granuloma in the lung. Granulomatous lesions were also found in the liver in 2/6, spleen and lymph node in one patient. Bone marrow aspiration and trephine showed granuloma (2), hypocellularity (2) and were normal in 2 patients. Lymphocyte subsets showed a low profile in 4/6 with raised double negative T cells in 5/6. Immunoglobulin level was normal in all except two. No Molecular diagnosis was made despite extensive investigation. Viral and microbiological investigations were negative. 4/6 required pulsed methylprednisolone at 10 mg/kg to control the lung disease. Two patients underwent Haemopoietic stem cell treatment (HSCT) due to refractory granulomatous disease and both are alive with significant improvement in pulmonary function. Conclusion: Children with GLILD have a more severe disease in comparison to adults and the majority do not fit the CVID criteria. 67% required intensive treatment with steroids.